2019
DOI: 10.1101/782987
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying differences in bile acid pathways for cholesterol clearance in Alzheimer’s disease using metabolic networks of human brain regions

Abstract: Alzheimer's disease (AD) is the leading cause of dementia, with metabolic dysfunction seen years before the emergence of clinical symptoms. Increasing evidence suggests a role for primary and secondary bile acids, the end-product of cholesterol metabolism, influencing pathophysiology in AD. In this study, we analyzed transcriptomes from 2114 post-mortem brain samples from three independent cohorts and identified that the genes involved in alternative bile acid synthesis pathway was expressed in brain compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Altered blood [93] and brain levels of BA [94] have been described. Interestingly, these metabolites were found to be highly relevant to drive our RF-based predictive process.…”
mentioning
confidence: 99%
“…Altered blood [93] and brain levels of BA [94] have been described. Interestingly, these metabolites were found to be highly relevant to drive our RF-based predictive process.…”
mentioning
confidence: 99%
“…Therefore, it is safer to assume that brain regions have different preferences for the use or production of these metabolites. Other vitamins and vitamin derivatives were mentioned for their neuroprotective effects in previous studies and interplay with fatty acids [62][63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, unsaturated fatty acids (especially hexanoyl-CoA and pentanoyl-CoA), retinoids and other vitamins are known to improve cognitive abilities [68][69][70][71]. Their neuroprotective effects were studied extensively and put forth clinically [64][65][66]. Thus, reintroducing them may ameliorate cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Baloni et al analyzed transcriptome data from 2114 postmortem brain samples from ROSMAP, Mayo Clinic and the Mount Sinai Brain Bank. They reconstructed brain region-specific metabolic networks and found that taurine transport, bile acid synthesis and cholesterol metabolism differed in AD patients versus healthy individuals ( Baloni et al, 2019 ). Some bile acids measured in brain tissue cannot be explained by the presence of enzymes responsible for their synthesis, raising the possibility that they could originate from the gut microbiome and get transported into the brain ( Baloni et al, 2019 ).…”
Section: Session 3: Pathogens and Microbiome In The Development Of Al...mentioning
confidence: 99%